Equine cervical remodeling during placentitis and the prepartum period: a transcriptomic approach. Issue 6 (5th May 2021) - El-Sheikh Ali, Hossam; Scoggin, Kirsten E; Ruby, Rebecca; Loynachan, Alan; Boakari, Yatta; Fernandes, Claudia; Dini, Pouya; Fedorka, Carleigh Elizabeth; Loux, Shavahn C; Esteller-Vico, Alejandro; Ball, Barry A
Abstract : Cervical remodeling is a critical component in both term and preterm labor in eutherian mammals. However, the molecular mechanisms underlying cervical remodeling remain poorly understood in the mare. The current study compared the transcriptome of the equine cervix (cervical mucosa (CM) and stroma (CS)) during placentitis (placentitis group, n   = 5) and normal prepartum mares (prepartum group, n   = 3) to normal pregnant mares (control group, n   = 4). Transcriptome analysis identified differentially expressed genes (DEGs) during placentitis (5310 in CM and 907 in CS) and during the normal prepartum period (189 in CM and 78 in CS). Our study revealed that cervical remodeling during placentitis was dominated by inflammatory signaling as reflected by the overrepresented toll-like receptor signaling, interleukin signaling, T cell activation, and B cell activation pathways. These pathways were accompanied by upregulation of several proteases, including matrix metalloproteinases ( MMP1, MMP2, and MMP9 ), cathepsins ( CTSB, CTSC, and CTSD ) and a disintegrin and metalloproteinase with thrombospondin type 1 motifs ( ADAMTS1, ADAMTS4, and ADAMTS5 ), which are crucial for degradation of cervical collagens during remodeling. Cervical remodeling during placentitis was also associated with upregulation of water channel-related transcripts ( AQP9 and RLN ), angiogenesis-related transcripts ( NOS3, ENG1, THBS1, and RAC2 ), and aggrecan ( ACAN ), a hydrophilic glucosaminoglycan, with subsequent cervical hydration. The normal prepartum cervix was associated with upregulation of ADAMTS1, ADAMTS4, NOS3 and THBS1, which might reflect an early stage of cervical remodeling taking place in preparation for labor. In conclusion, our findings revealed the possible key regulators and mechanisms underlying equine cervical remodeling during placentitis and the normal prepartum period.